EFFECT OF FINANCIAL PERFORMANCE, BUSINESS RISK, AND SALES GROWTH ON CAPITAL STRUCTURE - Agus Dwi Cahya; Prahadhita Nerissa Putri; Retno Dwi Pangesti; Selvi Wahyuningsih (Faculty of Economic and Business, University of Pasundan, 2021)
The purpose of this study was to determine the effect of financial performance, business risk, and sales growth on capital structure. The population in this study was 1 (one) Micro, Small and Medium Enterprises (UMKM) Lanthing batik fashion craft in Gunting village, Gilangharjo, Pandak sub-district, Bantul regency. The type of research used in this research is descriptive research using a quantitative approach. Types and sources of data obtained from primary data from UMKM Batik Lanthing with interview data collection techniques, documentation, and observations. The analysis technique used in this study is multiple linear regression analysis, t test, and F test. The results of this study indicate that the financial performance, the business risk variable does not have a significant effect on the capital structure, and the sales growth variable has a significant effect on the capital structure. It can be concluded that the variables of financial performance, business risk, and sales growth together have a significant effect on the capital structure.